Corn, cotton, and peanut response to row spacing, seeding rate, and irrigation system. Issue 3 (4th May 2023) - Sorensen, Ronald B.; Lamb, Marshall C.; Butts, Christopher L.
ABSTRACT: Planting crop rows closer to a drip line water source should result in increased seed development, greater crop yield, and possible water savings and may reduce seeding rate without affecting yield, resulting in lower seed costs. This research documents the yield response of corn, cotton, and peanut planted in two crop row spacings (0.76 and 0.91 m), at two seeding rates (1× and 0.5×), at four locations, and two irrigation systems (sprinkler and drip). Crops were managed using best management practices for maximum yield. Irrigation events were scheduled to minimize soil water stress. There was no yield response across all crops, locations, or irrigation systems for 0.76 versus 0.91-m crop row spacing. The 0.5× seeding rate in drip irrigation and across all sites reduced corn yield and revenue by an average 1572 kg/ha and -94/ha, respectively. The 0.5× seeding rate in drip irrigation did not decrease yield in cotton or peanut and revenue above seed cost averaged 16 and 95/ha, respectively. It should be noted that in cotton and peanut, the 0.5× seeding rate may impose a greater risk for yield loss due to low germination due to drought (cotton) and increased disease (peanut). In conclusion, moving the seed row closer to a drip lateral had no effect on yield and using 0.5× seeding rates for these crops may not always be economical.